2016
DOI: 10.1002/ijc.30456
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-principle study of a novel cervical screening and triage strategy: Computer-analyzed cytology to decide which HPV-positive women are likely to have ≥CIN2

Abstract: A challenge in implementation of sensitive HPV-based screening is limiting unnecessary referrals to colposcopic biopsy. We combined 2 commonly recommended triage methods: partial HPV typing and “reflex” cytology, evaluating the possibility of automated cytology. This investigation was based on 1,178 exfoliated cervical specimens collected during the enrollment phase of The Study to Understand Cervical Cancer Early Endpoints and Determinants (SUCCEED, Oklahoma City, Oklahoma). We chose a colposcopy clinic popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Adequate recruitment, training and retention of cytology staff in an era of HPV primary screening may prove challenging and efforts to address this are required. A novel approach to automated cytology that achieves performance similar to expert manual evaluation may serve as mitigation to these challenges …”
Section: Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate recruitment, training and retention of cytology staff in an era of HPV primary screening may prove challenging and efforts to address this are required. A novel approach to automated cytology that achieves performance similar to expert manual evaluation may serve as mitigation to these challenges …”
Section: Cytologymentioning
confidence: 99%
“…A novel approach to automated cytology that achieves performance similar to expert manual evaluation may serve as mitigation to these challenges. 17…”
Section: Cytologymentioning
confidence: 99%
“…Progression to invasion involves the accumulation of genetic errors. The overall process is complex and includes a number of genetic and epigenetic alterations [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Cytological abnormalities of LSIL or more severe. 3 Cytological abnormalities of HSIL or more severe.…”
Section: Dear Editormentioning
confidence: 99%
“…A slide with a high severity-assigned score has a high probability of cellular abnormality, whereas a slide with a low severity-assigned score is more likely to be negative. Recently, in a proof-of-principle study, Schiffman et al [3] found that it is possible to triage HPV-positive women using the same screener (FocalPoint) with a redesigned algorithm.The above results are promising and indicate that automated cervical cytology screening could be an appropriate method by which to identify women at the highest risk of cancer precursor lesions among HPV-positive subjects. However, the decision regarding its introduction as a triage tool must be evaluated by additional clinical studies to estimate if this strategy is optimal for women in terms of benefits versus harms.…”
mentioning
confidence: 99%